Appraising executive compensation ESG-based indicators using analytical hierarchical process and Delphi techniques - Matemane, Reon; Moloi, Tankiso; Adelowotan, Michael Olajide (Journal of risk and financial management, 2022)
Economic, social and governance (ESG) have become topical subjects amidst the deleterious effects of climate change, inequality and similar pressing challenges facing the people and the planet. The main objective of this study was to rank the importance of both the pillars within the ESG model and the five indicators beneath each pillar for the purposes of executive compensation plans through the Analytical hierarchical process (AHP). It is not known which pillar within the ESG model should be prioritised by companies operating in a developing economy context such as South Africa, and neither is it known which of the available indicators should be prioritised when designing executive compensation plans. AHP and pairwise comparison is employed in prioritising important pillars and indicators. The environmental pillar is identified to be the most important among the three pillars. Indicators that are prioritised mirror both the environmental and socio-economic challenges prevalent in South Africa as an emerging economy. Companies' boards, remuneration committees, investors and policymakers can use the ESG-based indicators that have been prioritised in this study in designing the executive compensation plans. AHP and pairwise comparison are novel approaches used to prioritise the important pillars within the ESG model and the underlying indicators.